Business Feasibility Analysis of Charcoal Production in Wanareja Village, Rimbo Ulu District, Tebo Regency - Evi Fauzani; Etty Siswati; Frisko Dwantara (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2026)
This study aims to analyze the feasibility of a wood charcoal business in Wanareja Village, Rimbo Ulu Subdistrict, Tebo Regency based on business aspects and investment indicators. This research is motivated by the high economic potential and the increasing demand for wood charcoal as an alternative energy source. The method used in this research is a quantitative descriptive approach. Data collection was carried out through interviews and observations to obtain primary data, as well as business records for secondary data. The results showed that the wood charcoal business is highly feasible to run. This feasibility is evidenced by a Net Present Value (NPV) of IDR 298,290,994.33, an Internal Rate of Return (IRR) of 43.305%, a Net Benefit Cost Ratio (Net B/C) of 14.69, and a relatively short Payback Period of 1 month and 4 days. This study contributes to the development of literature on local resource-based business feasibility analysis and provides practical implications for business actors and local governments as a basis for making investment and business development decisions.